Automated Synthesis of New Quinoxalinetacrines. Issue 21 (5th June 2020) - Bautista‐Aguilera, Óscar M.; Ismaili, Lhassane; Chioua, Mourad; Iriepa, Isabel; Ángeles Martinez‐Grau, Marìa; Beadle, Christopher D.; Vetman, Tatiana; López‐Muñoz, Francisco; Marco‐Contelles, José
Abstract: Tacrine was the first acetylcholinesterase inhibitor approved for the treatment of Alzheimer's disease although its use has been limited and finally abandoned because of side effects including hepatic toxicity. Based on 1, 2, 3, 4‐tetrahydroquinolino[2, 3‐ b ]quinoxalin‐12‐amine (QT78 ), a recently reported cholinesterase inhibitor, less toxic and potent than tacrine as acetylycholinesterase inhibitor, but more selective against butyrylcholinesterase, herein we report the synthesis of novel quinoxalinetacrines QT1‐11, a series of hybrids designed by juxtaposition of tacrine and quinoxaline. The target compounds have been obtained in moderate yields from 3‐aminoquinoxaline‐2‐carbonitrile and suitable commercially available ketones, under microwave‐promoted Friedländer reactions catalyzed by aluminium trichloride or indium trichloride. These compounds were synthesized remotely in Eli Lilly's Automated Synthesis Laboratory as part of their Open Innovation Drug Discovery program. Abstract : QuinoxalineTacrines QT1‐11, designed by juxtaposition of tacrine and quinoxaline, have been obtained from 3‐aminoquinoxaline‐2‐carbonitrile and suitable commercially available ketones, by Lewis‐acid catalyzed Friedländer reaction.